Investigation of Flow Characteristics of Iron-Ore and Water Slurry - Kumar, Sagar (My University, 2018)
The rheological characteristics of uni-modal and multivariate iron-ore slurry have been examined. The study aimed to investigate the physical, chemical and morphological characteristics of iron-ore particles. Present study also includes the experimental investigation of flow characteristics of iron-ore slurry. The physical, chemical and mineralogical properties such as surface microstructure, chemical composition, crystalline phase analysis, particle size distribution (PSD), shape, static settled concentration, slurry density and pH of iron-ore were carried out prior to examination of rheological characteristics of iron-ore slurry. The surface microstructure was investigated by using Scanning electron microscopy (SEM) technique. The chemical composition was determined by using Electron dispersive spectroscopy (EDS) technique. The crystalline phases present in iron-ore particles were examined by using X-Ray Diffraction (XRD) technique. Particle size distribution of iron-ore particles was carried out by using British standard sieves. Bench-scale tests were performed to determine the density and static settled concentration of iron-ore slurry. The various parameters related to shape such as particle shape factor, sphericity and surface smoothness were determined by using numerical simulations. The simulations were carried out by digital interpretations by reading the pixel and grey value information present in a particular SEM micrograph. The iron-ore particles were found irregular in shape with knife edges. The circularity and sphericity of hematite iron-ore was lies in range 0.31-0.55 and 0.30-0.56 respectively whereas 0.34-0.51 and 0.36-0.54 respectively for magnetite iron-ore. The sphericity and circularity of iron-ore particles was found to be very low which indicated that particles of iron have irregular and conical shape. The pH value of uni-model and multivariate iron-ore slurry was lie in the range of 8.92 to 9.08. The experimental investigation of rheological characteristics of multiphase slurry has been devoted to understanding ability of material flow. The rheological experiments were conducted by using standard rotational rheometer (manufactured by: Rheolab Q-C, APC Ltd. Germany). The uni-modal sample of slurry was designated as sample S-1 and multivariate slurry sample was designated as sample S-2. The rheological experiments were conducted with varying solid concentration from 30 to 60% by weight. The uni-modal slurry exhibits almost Newtonian fluid flow-behavior up to the solid concentration of 30% by weight. However, in case multivariate slurry the flow behavior was found to be pesudoplastic at low concentration. Also, the apparent viscosity of slurry is highly influenced by the applied shear rate and the solid concentration. It has been noticed that the slurry viscosity is very high at initial phase afterward it starts decreasing with further increase in shear rate. On the other hand, slurry viscosity increases with increase in solid concentration. The experimentation was further extended to study the effect of addition of finer particles on the rheology of uni-modal and multivariate slurry. The optimum reduction in viscosity was found at blending concentration of 30% by weight for the slurry of sample S-2 whereas, blending concentration of 20% by weight found to be optimum for the slurry prepared by sample S-2.
Keywords: Rheology, particle size distribution, bimodal, circularity factor, sphericity